PENINGKATAN HASIL BELAJAR TEMATIK DENGAN MODEL PEMBELAJRAN KOOPERATIF TIPE SNOWBALL THROWING PADA SISWA KELAS V DI SDN 019 RAMBAH - Nursahadah Dasopang (STKIP ROKANIA, 2019)
This study aims to improve the thematic learning outcomes of fifth grade students at SDN 019 Rambah. This type of research is classroom action research. The subjects in this study were fifth grade students of SDN 019 Rambah, Rambah District, Rambah Regency with a total of 24 students. The results obtained from this study, namely the learning outcomes of students in class V SDN 019 Rambah increased in the first cycle amounted to 79.16% with an average of 80.6 then the second cycle increased to 91.66% with an average of 88.4% . While the observations of teacher and student activities also increased. The success of researcher activity in cycle I was 92.85%, increasing in cycle II to 96.42%. Thus the application of the snowball throwing cooperative learning model can improve the thematic learning outcomes of fifth grade students at SDN 019 Rambah.